A numerical study on the influence of internal corrugated reinforcements on the biaxial bending collapse of thin-walled beams. (November 2019) - Vignjevic, Rade; Liang, Ce; Hughes, Kevin; Brown, Jason C.; De Vuyst, Tom; Djordjevic, Nenad; Campbell, James
Abstract: The Heat Treatment Forming and in-die Quench (HFQ) process allows for manufacturing of more complex geometries from Aluminium sheets than ever before, which can be exploited in lightweight automotive and aerospace structures. One possible application is manufacturing thin walled beams with corrugated internal reinforcements for complex geometries. This work considers different internal reinforcements (C-section and corrugated) to improve the energy absorption properties of thin walled rectangular beams under uniaxial and biaxial deep bending collapse, for loading angles ranging from 0 to 90 deg, in 15° increments. Using LS-DYNA simulations experimentally validated through unreinforced metallic tubes under quasi-static bending collapse, the finite element results demonstrate the stabilising effect of the reinforcements and an increase in the buckling strength of the cross section. Corrugated reinforcements showed a greater potential for increasing specific energy absorption (SEA), which was supported by investigating key geometric parameters, including corrugation angle, depth and number. This favourable response is due to an increased amount of material undergoing plastic deformation, which consequently improves performance of the beam undergoing post buckling and deep collapse. This concept is applicable to vehicle and aircraft passive safety, with the requirement that the considered geometries are manufacturable from Aluminium Alloys sheet only, using the HFQ process. Highlights: Uniaxial and Biaxial bending collapse of thin-walled beams with varying internal reinforcements. Corrugated reinforcements increase the buckling strength of a cross section under post-buckling and deep collapse. Increasing corrugation depth or the number of corrugations can increase the specific energy absorption of reinforced tubes This corrugated reinforcement concept is applicable to vehicle and aircraft passive safety